Early chromatin unfolding by RUNX1: a molecular explanation for differential requirements during specification versus maintenance of the hematopoietic gene expression program - Hoogenkamp, Maarten; Lichtinger, Monika; Krysinska, Hanna; Lancrin, Christophe; Clarke, Deborah; Williamson, Andrew; Mazzarella, Luca; Ingram, Richard; Jorgensen, Helle; Fisher, Amanda; Tenen, Daniel G; Kouskoff, Valerie; et al. (Blood, 2009)
At the cellular level, development progresses through successive regulatory states, each characterized by their specific gene expression profile. However, the molecular mechanisms regulating first the priming and then maintenance of gene expression within one developmental pathway are essentially unknown. The hematopoietic system represents a powerful experimental model to address these questions and here we have focused on a regulatory circuit playing a central role in myelopoiesis: the transcription factor PU.1, its target gene colony-stimulating-factor 1 receptor (Csf1r), and key upstream regulators such as RUNX1. We find that during ontogeny, chromatin unfolding precedes the establishment of active histone marks and the formation of stable transcription factor complexes at the Pu.1 locus and we show that chromatin remodeling is mediated by the transient binding of RUNX1 to Pu.1 cis-elements. By contrast, chromatin reorganization of Csf1r requires prior expression of PU.1 together with RUNX1 binding. Once the full hematopoietic program is established, stable transcription factor complexes and active chromatin can be maintained without RUNX1. Our experiments therefore demonstrate how individual transcription factors function in a differentiation stage-specific manner to differentially affect the initiation versus maintenance of a developmental program.